Uridine diphosphate release mechanism in O-N-acetylglucosamine (O-GlcNAc) transferase catalysis - She, Nai; Zhao, Yuan; Hao, Jingjing; Xie, Songqiang; Wang, Chaojie (Biochimica et biophysica acta. General subjects, 2019)
O-linked N-acetylglucosamine transferase (OGT) is an essential enzyme that catalyzes the covalent bonding of N-acetylglucosamine (GlcNAc) to the hydroxyl group of a serine or threonine in the target protein. It plays an important role in many important cellular physiological catalytic reactions. Here, we determine the binding mode and the binding free energy of the OGT product (uridine diphosphate, UDP) as well as the hydrogen-bond-dependent release mechanism using extensive molecular dynamic simulations. The Lys634, Asn838, Gln839, Lys842, His901, and Asp925 residues were identified to play a major role in the UDP stabilization in the active site of OGT, where hydrogen bonding and π-π interactions mainly occur. The calculations on the mutant forms support our results. Sixteen possible release channels were identified while the two most favorable channels were determined using random acceleration molecular dynamics (RAMD) simulations combined with the constant velocity pulling (PCV) method. The thermodynamic and dynamic properties as along with the corresponding mechanism were determined and discussed according to the umbrella sampling technique. For the most optimal channel, the main free energy barrier is 13 kcal/mol, which probably originates from the hydrogen bonds between UDP and the Ala896 and Asp925 residues. Moreover, the unstable hydrogen bonds and the rollback of the ligand likely cause the other two small obstacles. This work clarifies the ligand transport mechanism in the OGT enzymatic process and is a great resource for designing inhibitors based on UDP or UDP-GlcNAc. [Display omitted] •Sixteen plausible channels for UDP transportation in OGT are detected.•The key residues that influence the UDP binding and release are identified.•The thermodynamic and dynamic properties for the most two favorable channels of UDP release are obtained.•Hydrogen-bond-dependent product release mechanism in OGT is first revealed.